Asymmetric Recruitment of β-Arrestin1/2 by the Angiotensin II Type I and Prostaglandin F2α Receptor Dimer - Fillion, Dany; Devost, Dominic; Sleno, Rory; Inoue, Asuka; Hébert, Terence E. (Frontiers in Endocrinology, 2019)
Initially identified as monomers, G protein-coupled receptors (GPCRs) can also form functional homo- and heterodimers that act as distinct signalling hubs for cellular signal integration. We previously found that the angiotensin II (Ang II) type 1 receptor (AT1R) and the prostaglandin F2α (PGF2α) receptor (FP), both important in the control of smooth muscle contractility, form such a functional heterodimeric complex in HEK 293 and vascular smooth muscle cells. Here, we hypothesize that both Ang II- and PGF2α-induced activation of the AT1R/FP dimer, or the parent receptors alone, differentially regulate signalling by distinct patterns of β-arrestin recruitment. Using BRET-based biosensors, we assessed the recruitment kinetics of β-arrestin1/2 to the AT1R/FP dimer, or the parent receptors alone, when stimulated by either Ang II or PGF2α. Using cell lines with CRISPR/Cas9-mediated gene deletion, we also examined the role of G proteins in such recruitment. We observed that Ang II induced a rapid, robust and sustained recruitment of β-arrestin1/2 to AT1R and, to a lesser extent, the heterodimer, as expected, since AT1R is a strong recruiter of both β-arrestin subtypes. However, PGF2α did not induce such recruitment to FP alone, although it did when the AT1R is present as a heterodimer. β-arrestins were likely recruited to the AT1R partner of the dimer. Gαq, Gα11, Gα12 and Gα13 were all involved to some extent in PGF2α-induced β-arrestin1/2 recruitment to the dimer as their combined absence abrogated the response, and their separate re-expression was sufficient to partially restore it. Taken together, our data sheds light on a new mechanism whereby PGF2α specifically recruits and signals through β-arrestin but only in the context of the AT1R/FP dimer, suggesting that this may be a new allosteric signalling entity.